Worksop Digital Marketing Promosi Penjualan Keripik Daun Kelor Hasil Industri Kreatif Mahasiswa Universitas Indo Global Mandiri - Agustina Heriyati; Fauziah Afriyani; Harsi Romli; Indah Pratiwi Putri; Mulyati Mulyati (I-Com: Indonesian Community Journal, 2024)
Moringa leaf chips are an innovative product from the creative industry of Indo Global Mandiri University students which has great potential to develop in local and international markets. However, the main challenge faced is the lack of knowledge and skills in digital marketing that can support product promotion and sales effectively. This workshop was held with the aim of increasing students' capacity in using digital marketing strategies to market Moringa leaf chips. This activity includes intensive training regarding creative content creation, social media management, search engine optimization (SEO), and the use of e-commerce. Apart from that, this workshop also provides mentoring and direct practice sessions to help participants apply the knowledge they have gained. It is hoped that the results of this workshop can increase students' knowledge about digital marketing, expand market reach, and increase sales of Moringa leaf chips as a superior product at Indo Global Mandiri University.